Cholesterol emboli syndrome. Issue 7268 (28th October 2000) - Dupont, Peter J; Lightstone, Liz; Clutterbuck, Elaine J; Gaskin, Gillian; Pusey, Charles D; Cook, Terry; Warrens, Anthony N
Abstract : Cholesterol embolism is a common but underrecognised complication arising from a variety of vascular insults